Simultaneous Schlieren-Shadowgraph Visualization and Temperature Measurement Fields of Fluid Flow Using One Color CCD Camera - Adrián Martínez-González; David Moreno-Hernández; Miguel León-Rodríguez; César Carrillo-Delgado; Enrique Cossío-Vargas (Sensors, 2022)
Visualizing two variables in the fluid flow requires a complex optical system to fulfill such a purpose. Furthermore, in these applications, measuring the temperature fields of the fluid is sometimes necessary. In this work, we use a color digital camera to record in one snapshot shadowgraph and two direction sensitivity Schlieren images. Furthermore, the Schlieren images obtained are used to measure temperature fields. The optical system, as main components, employs an rgb Light Emitting Diode (LED), two knife edges represented by shortpass and longpass ultra-thin filters, and a color digital camera. The results of this study show that shadowgraph images are contaminated with the crosstalk effect, and correction against it was applied. On the other hand, the reached resolution of the optical system to measure temperature values is approximately one degree.